Antihyperlipidemic potential of Eugenia caryophyllus extract in Wistar rats - Roma Ghai; Kandasamy Nagarajan; Vinay Kumar; Parul Grover (International Journal of Phytomedicine, 2014)
Objective: The present study was aimed to evaluate the antihyperlipidemic activity of the aqueous ethanolic extract of Eugenia caryophyllus in triton induced hyperlipidemia. Methods: Antihyperlipidemic activity was evaluated using Triton X 100 induced hyperlipidemia in rats as an experimental model. Hyperlipidemia was induced in rats by a single intraperitoneal (ip) injection of Triton X 100 (400 mg/kg b.w.) The aqueous ethanolic extract of Eugenia caryophyllus extract was administered at two different doses of 200mg/kg and 400mg/kg for 7 days to hyperlipidemic rats. Atorvastatin was used as a reference standard. Serum triglycerides, total cholesterol, HDL-C, LDL-C and VLDL-C, atherogenic index and glucose were determined to assess the antihyperlipidemic activity. Result: It was found that the aqueous ethanolic extract of Eugenia caryophyllus at the doses of 200mg/kg and 400mg/kg showed a significant decrease in the levels of serum total cholesterol, triglycerides, LDL-C, VLDL-C, glucose and significant increase in the level of serum HDL-C. Conclusion: The current study provided a strong evidence that the Eugenia caryophyllus extracts at both the doses (200mg/kg and 400mg/kg) possess significant antihyperlipidemic activity. The dose of 400mg/kg had a higher beneficial effect and its efficacy was similar to that of Atorvastatin in treating hyperlipidemia. However, further study is needed to understand the precise mechanism.